Proceedings of the 8th International Conference on Body Area Networks 2013
DOI: 10.4108/icst.bodynets.2013.253699
|View full text |Cite
|
Sign up to set email alerts
|

Energy Expenditure Estimation using Smartphone Body Sensors

Abstract: Energy Expenditure Estimation (EEE) is an important step in tracking personal activity and preventing chronic diseases such as obesity, diabetes and cardiovascular diseases. Accurate and online EEE utilizing small wearable sensors is a difficult task, primarily because most existing schemes work offline or using heuristics. In this work, we focus on accurate EEE for tracking ambulatory activities (walking, standing, climbing upstairs or downstairs) of a common smartphone user. We used existing smartphone senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 19 publications
(21 reference statements)
0
20
0
Order By: Relevance
“…However, with the phone carried in the back pocket, the likelihood of undercounting steps increases, due to extra oscillations caused by the relaxation of the gluteus maximus during the walking cycle. A related study found smartphones to be more accurate for energy expenditure prediction than wearable accelerometers [13]. Smartphones feature barometers which can be appropriated to distinguish between walking up or down stairs which generate different amounts of energy expenditure.…”
Section: Related Workmentioning
confidence: 98%
See 1 more Smart Citation
“…However, with the phone carried in the back pocket, the likelihood of undercounting steps increases, due to extra oscillations caused by the relaxation of the gluteus maximus during the walking cycle. A related study found smartphones to be more accurate for energy expenditure prediction than wearable accelerometers [13]. Smartphones feature barometers which can be appropriated to distinguish between walking up or down stairs which generate different amounts of energy expenditure.…”
Section: Related Workmentioning
confidence: 98%
“…Wearables typically support eyes-and hands-free interaction, which allows them to be used in active contexts, such as walking or running. Pedometry, i.e, step counting, is used in various mobility related applications, such as physical activity tracking [13] or infrastructure-free indoor navigation [8]. Pedometry can be achieved with wearable accelerometers, e.g., Fitbit [2], or using inertial sensors that have become ubiquitous in smartphones [6] and HMDs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, [6] attempts to work on data compression on mobile devices to improve battery life. Similarly, the work of [7] explored more accurate Energy Expenditure Estimates (EEE) of small wearable sensors. The limitations of personal fitness devices has been noted by [8], who state that "sensor measures are subject to various limitations like resolution errors, calibration variability, response time" and "precision depending on working conditions".…”
Section: Related Workmentioning
confidence: 99%
“…Misra and Lim [16] used an asynchronous querying technique to save 70% energy. Pande et al [18] proposed the use of smartphone sensors at reduced frequency for detecting Energy Expenditure Estimation. On the other hand the work by Wang et al [25] offload data processing to the cloud for better energy management.…”
Section: Related Workmentioning
confidence: 99%